Age and body composition influence TSH concentrations after administration of rhTSH - Holthausen, F. F.; von Müller, F.; Happel, C.; Kranert, W. T.; Grünwald, F. (Nuklearmedizin - NuclearMedicine, 2015)
Aim: Previous studies listed body surface area (BSA), lean body mass (LBM), and age as modifying factors on the TSH concentrations after administration of recombinant human thyrotropin (rhTSH). The purpose of this study was to identify the main modifying factors on serum TSH levels and to compare the stimulation via single rhTSH injection after a short thyroid hormone withdrawal (THW) with that of the standard stimulating protocol. Patients, methods: 106 patients with differentiated thyroid cancer (DTC) undergoing radioiodine therapy (RIT) after rhTSH administration were obtained through chart review. Two groups were evaluated: Group I was treated with a single rhTSH administration after two weeks of T3 therapy followed by one week of THW. Group II was stimulated according to the international standard protocol via rhTSH injections for two consecutive days. Serum TSH concentrations were documented prior to rhTSH administration (day 1 TSH), one day after (day 3 TSH) and 3–6 days after (mean 4.2 days, day 6 TSH) the last rhTSH injection. The following data was collected: age, gender, weight, height, BMI, LBM, BSA, residual thyroid tissue, CRP, creatinine, GFR, liver enzymes, alkaline phosphatase, cholesterol, and triglycerides. Results: Group I: Age combined with anthropometric factors like BMI (TSH increase and day 6 TSH), BSA (TSH decrease), and gender (day 6 TSH) are the main modifying factors on serum TSH concentrations after rhTSH administration. Group II: Age and lean body mass (LBM) showed a significant impact on day 3 TSH, TSH increase (day 3-day 1), and TSH decrease (day 6-day 3). Day 6 TSH was found to be influenced by GFR (group II). Conclusion: Age and anthropometric parameters have significant independent influence on TSH concentrations after rhTSH injection in both groups. Anthropometric parameters (BSA, LBM) and demographic parameters (female gender) show strong influence on TSH concentrations. Further research should be conducted to examine the influence of body compartments on TSH levels through measuring total body water.
Keywords: Recombinant human TSH; rhTSH; thyroid cancer; radioiodine therapy; age; body surface area; lean body mass